The Role of Tourism in Regional Development (Case of Klaten District) - Sujali, Sujali (Forum Geografi, 1996)
The title of the reasearch is the role of tourism in regional development. This is a case study in Klaten regency because of the appearance and the activities on tourism to support the regional and national development. The purpose of this research are 1) to explore the potency, the spreads of regional tourism resorts; 2) to describe the supporting facilities to regional tourism towards the regional income and development. The data of this research are secondary data taken from the Regional Tourism Service Office, Regional Income Service Office, Agency for Planning of Regional Development, and the related department. The data are also taken from the interview of outstanding persons. The method of analysing the data is relative descriptive analysis supported by tendency analysis gained from time series data.Demand and supply approachs are used to develop the tourism. Based on the data we an know the profiles of the tourists. The tend to visis (the tourism of) entertainments. Most tourists are adult and old. The greatest resource of the Original Regional Income (PAD) is from local retribution. This include the income from (the tourism of) entertainments and recreation which have low contribution. The role of tourism in Klaten regency should be kept increasing to support the Original Regional Income and development. To keep the tourism inreaseing the supported capital, engineering, and skills from the developers are badly neede. It is important to increase the role of Tourism Service and managing the tourism. It an be concluded that tourism hasnât improved yet the regional income and economy. That is why the tourism should be kept increasing.